IoT based traffic congestion control for environmental applications - Gherbi, Chirihane; Roumaissa, Doudou (Informatica, 2021)
Recently, the demands of the Internet of Things (IoT) have been steadily growing .The main idea of the Internet of Things (IoT) is to revolutionize the current Internet by enriching it with a large number of intelligent objects that communicate with each other. Heterogeneous communication technologies are integrated into the Internet to achieve the IoT application. The function of these objects is to collect data from sensors, process it, and communicate it. Therefore, sensors are main features of IoT. The Heterogeneous Wireless sensor network (HWSN) is a key technology element of the Internet of Things (IoT), which is considered as the future evolution of the Internet. The integration of HWSNs into IoT makes communication with any type of object possible and opens the gates to a multitude of application areas. We have proposed: (Load-Balancing based Clustering Multipath routing protocol for Heterogeneous sensor networks). After having detailed the functioning of our protocol, we present the realization of the simulations by the NS3 simulator, whose objective is to allow us to evaluate the performances of the proposed (Load-Balancing based Clustering Multipath routing protocol for HWSN) by comparing the results with the two protocols: (Weight based clustering in wireless sensor networks) and (Distributed Energy efficient Adaptive Clustering Protocol). We thus take into account several metrics for the performance of evaluation. We also note that the proposed protocol is 47% better than DEACP with respect to fist node die, and 35% better than WBCHN with respect to last node die while maintaining the average data transmission delay. We were able to show through the simulation results obtained that the objectives have been reached.